2019
DOI: 10.4274/jus.galenos.2019.2343
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization of Ureteral Double-J Stents in Patients with Negative Urine Culture

Abstract: Amaç: Üreteral çift-J stentler üroloji uygulamalarında yoğun olarak kullanılmaktadır. Prospektif bir çalışma ile idrar kültürü negatif olan hastalarda üreteral çift-J stentlerdeki bakteriyel kolonizasyon ve baskın mikroorganizmaların araştırılması amaçlanmıştır. Gereç ve Yöntem: Otuz beş ardışık hastadan çıkartılan 35 çift-J stent incelendi. Sistoskopik olarak çıkartılan stentler üst, orta ve alt olarak üç parçaya ayrılarak stent çıkartılmadan hemen önce alınan idrar örneği ile birlikte mikrobiyolojik inceleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The most common microorganism before stenting in our study was E. coli , which is consistent with the data from other researchers who report that detection of E. coli colonizing stents is one of their most frequent findings [ 17 , 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The most common microorganism before stenting in our study was E. coli , which is consistent with the data from other researchers who report that detection of E. coli colonizing stents is one of their most frequent findings [ 17 , 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…There are only a few studies on bacterial colonization on DJ stents in the literature; 10,11 however, none of them compare the different zones of the DJ stent. Yeniyol et al evaluate DJ stent by culture in 61 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between indwelling time and microbial stent colonization has been extensively reported (60,91). In a clinical study analyzing 93 stents from 71 patients, Riedl et al (86) reported that all ureteral stents were colonized at 27 to 73 days from insertion, while 69% of stents were colonized at 1 to 48 days from insertion.…”
Section: Key Bacteria In Biofilms: the Significance Of Optimal Remova...mentioning
confidence: 85%
“…While one study (91) reported that bacterial colonization was present in all regions of patient-retrieved stents in 71% of cases, other reports have shown different results. For instance, Aydin et al (71) showed that the colonization rate was the same for each part of the stent in 30% of the cases.…”
Section: Distribution Patterns Of Biofilm and Encrustation In Uretera...mentioning
confidence: 90%